THE EFFECT OF THE TEAMS GAMES TOURNAMENT (TGT) LEARNING METHOD ON THE COOPERATIVE ABILITY OF ELEMENTARY SCHOOL STUDENTS - Lia Lesmana; Anggy Giri Prawiyogi; Yayan Alpian (Jurnal Cakrawala Pendas, 2026)
The low level of student cooperation skills in elementary schools remains a common problem, primarily due to the dominance of teacher-centered learning, which limits student interaction and active participation. This condition results in students having less opportunity to develop social skills such as cooperation, communication, and collective responsibility. One alternative that can be implemented to overcome this problem is the Teams Games Tournament (TGT) cooperative learning model, which integrates teamwork with games and academic competitions. This study examines the effectiveness of the TGT method in improving students' cooperation skills. The study used a quantitative approach with a quasi-experimental pretest-posttest control group design. The subjects were fifth-grade students divided into experimental and control groups. Data were collected through a Likert-scale questionnaire that measured indicators of cooperation skills. Data analysis was carried out using normality and homogeneity tests, and hypothesis testing with a Paired Samples T-Test. The results of the data analysis showed that there was a significant difference between student outcomes before and after treatment. In conclusion, it shows that the use of the TGT method based on tournament games in this learning is effective in improving students' cooperation skills in groups. This method makes learning more meaningful, enjoyable, and can increase student engagement in learning. Rendahnya kemampuan kerja sama siswa di sekolah dasar masih menjadi permasalahan yang sering dijumpai, terutama akibat dominasi pembelajaran yang berpusat pada guru sehingga membatasi interaksi dan partisipasi aktif siswa. Kondisi ini menyebabkan siswa kurang memiliki kesempatan untuk mengembangkan keterampilan sosial seperti kerja sama, komunikasi, dan tanggung jawab kolektif. Salah satu alternatif yang dapat diterapkan untuk mengatasi permasalahan tersebut adalah metode pembelajaran kooperatif tipe Teams Games Tournament (TGT) yang mengintegrasikan kerja sama tim dengan permainan dan kompetisi akademik. Penelitian ini mengkaji efektivitas metode TGT dalam meningkatkan kemampuan kerja sama siswa. Penelitian menggunakan pendekatan kuantitatif dengan desain quasi eksperimen pretest-posttest control group. Subjek penelitian adalah siswa kelas V yang dibagi menjadi kelompok eksperimen dan kontrol. Data dikumpulkan melalui angket skala Likert yang mengukur indikator kemampuan kerja sama. Analisis data dilakukan dengan uji normalitas dan homogenitas, serta uji hipotesis dengan Paired Sample T-Test. Hasil analisis data menunjukkan bahwa terdapat perbedaan yang signifikan antara hasil siswa sebelum dan sesudah perlakuan. Kesimpulannya, menunjukkan bahwa penggunaan metode TGT berbasis permainan tournament pada pembelajaran ini efektif dalam meningkatkan kemampuan kerja sama siswa dalam kelompok. Metode ini membuat pembelajaran lebih bermakna, menyenangkan, dan dapat meningkatkan keterlibatan siswa dalam pembelajaran.